Gender-responsive participatory videos: a guide for facilitators. - Kawarazuka, Nozomi; Kharlyngdoh, A.; Marbaniang, E.; Syndor, A. (International Potato Center, 2017)
Participatory-video is a research technique in which farmers film and publicly screen interviews with their peers. It is a powerful tool to build relationships between researchers and farmers and collect the real voices of the different social groups in the community. This guide has been prepared for researchers and development practitioners who are interested in applying this technique.